2021
DOI: 10.3390/jcm10245749
|View full text |Cite
|
Sign up to set email alerts
|

Trends in Hospital Admissions and Death Causes in Patients with Systemic Lupus Erythematosus: Spanish National Registry

Abstract: Background: the admission and death causes of SLE patients might have changed over the last years. Methods: Analysis of the Spanish National Hospital Discharge database. All individuals admitted with SLE, according to ICD-9, were selected. The following five admission categories were considered: SLE, cardiovascular disease (CVD), neoplasm, infection, and venous-thromboembolic disease (VTED), along four periods of time (1997–2000, 2001–2005, 2006–2010, and 2011–2015). Results: The admissions (99,859) from 43.43… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

3
7
0

Year Published

2022
2022
2025
2025

Publication Types

Select...
6
2

Relationship

3
5

Authors

Journals

citations
Cited by 16 publications
(13 citation statements)
references
References 45 publications
3
7
0
Order By: Relevance
“…In addition to the importance of opportunistic infections in the immunosuppressed patient such as respiratory tract, abdominal, skin and soft tissue or central nervous system foci, as well as those produced by parasitic, fungal or zoonosis microorganisms, our results highlighted sepsis as a disproportionate cause of death in patients with lupus. Similar findings have been described previously, and even Singh and Cleveland recently showed that sepsis overtook pneumonia as the most common infection leading to admission in patients with SLE in the USA 18 19. Again, the striking mortality rate described in our population is especially noteworthy compared with what would be expected among young patients 12 22…”
Section: Discussionsupporting
confidence: 90%
See 1 more Smart Citation
“…In addition to the importance of opportunistic infections in the immunosuppressed patient such as respiratory tract, abdominal, skin and soft tissue or central nervous system foci, as well as those produced by parasitic, fungal or zoonosis microorganisms, our results highlighted sepsis as a disproportionate cause of death in patients with lupus. Similar findings have been described previously, and even Singh and Cleveland recently showed that sepsis overtook pneumonia as the most common infection leading to admission in patients with SLE in the USA 18 19. Again, the striking mortality rate described in our population is especially noteworthy compared with what would be expected among young patients 12 22…”
Section: Discussionsupporting
confidence: 90%
“…Other groups have previously analysed the causes of death in patients with SLE worldwide with different results, sometimes limited by sample size and monocentric design 4 5 7 11–15. Our nationwide analysis indeed confirms that infection has surpassed lupus itself as the main cause of death in this population, according to the increasing number of deaths due to infection during the last decades reported by others 4 8 16–19. Moreover, the risk of infection is particularly worrisome at a younger age, as our data confirmed, although it is not limited to this group.…”
Section: Discussionsupporting
confidence: 83%
“…From this perspective, certain conditions, such as heart failure, liver disease and chronic kidney disease, typically related to disease damage or subsequent treatments, were more frequent in SADs patients than in the general population and were, in turn, the main determinants of mortality in SAD patients in our study. Therefore, we believe that these findings strengthen the view that the best strategy to avoid fatal outcomes from COVID-19 in this population requires that first, in order to avoid chronic and irreversible organ damage, there is prompt and effective treatment of flares, with less toxic drugs and schemes, as a priority in these patients [ 16 , 38 ]. Second, vaccination policies and regimes must be individualized for individuals with SADs, taking into account that these patients must be at higher risk, even at a younger age, due to a higher rate of baseline comorbidities and prior chronic organ damage [ 39 ].…”
Section: Discussionmentioning
confidence: 72%
“…It records information from all patients discharged at hospitals/clinics across the country since the nineties [ 14 ]. Prior studies have been performed using this registry for other illnesses, including infectious diseases and SADs, and have demonstrated its high value for producing estimates of current burden and time trends for different clinical conditions at a national level [ 15 , 16 ].…”
Section: Methodsmentioning
confidence: 99%
“…15 Previous studies, in other geographic regions, mainly Europe, have also reported a decrease in hospitalization trends in the last decade. 14,16,17 . In our country, the reduction in hospitalization rate during 2011–2019 cannot be attributed to the use of new biological therapies approved for SLE in the last decade, like belimumab, since there is limited access to those therapies.…”
Section: Discussionmentioning
confidence: 99%